UPAYA MENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MENGGUNAKAN MODEL PEMBELAJARAN IMPROVE - Tety Septiani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
This research aims to improve students' critical thinking skill using IMPROVE learning model. The subject of this research were VII D grade students of SMP Negeri 9 Purwokerto in the academic year of 2016/2017, consisted of 18 male students and 18 female students. This research employed classroom action research with 3 cycles consisted of planning, acting, observing, and reflecting. In order to know students' critical thinking skill, the researcher used intrument of essay test given in the end of each cycle. The results indicate that students' critical thinking skill improves in cycle I with the mean score is 53.56; then it improves in cycle II with the mean score is 67.87; and it improves in cycle II with the mean score is 77.44. It can be concluded that IMPROVE learning model can improve students' critical thinking skill at VII D grade students of SMP Negeri 9 Purwokerto